Indium based metal-organic framework/carbon nanotubes composite as a template for In2O3 porous hexagonal prisms/carbon nanotubes hybrid structure and their application as promising super-capacitive electrodes. (July 2022) - Farbod, Fatemeh; Mazloum-Ardakani, Mohammad; Naderi, Hamid Reza; Mirvakili, Ali; Wang, Mengjiao; Shinde, Dipak V.; Dante, Silvia; Salimi, Pejman; Lauciello, Simone; Prato, Mirko
Highlights: Convenient synthesize of Interweaved MIL 68 (In) with multi wall carbon nanotubes nanocomposite. High specific capacitances of 601 Fg−1 at the scan rate of 5 mVs−1 and 473 Fg−1 at 1 Ag−1. Symmetric supercapacitor device with SC of 314 Fg−1 at the scan rate of 2 mVs−1, and 95% cycle stability after 4000. Abstract: The development of porous nano/microsctructural materials, has a major focus to provide impressive electrochemical features in energy storage technology. Metal-organic frameworks (MOFs) are emerging as talented materials in supercapacitors due to their intrinsic porosity properties, which can be well-controlled through molecular engineering. As smart pathways, utilizing MOFs as templates for generating carbon, metal oxide, and hydroxides, etc. materials, or hybridized MOFs have shown to be quite beneficial. MOF Hybridizing with carbon nanotubes helps considerably eliminate the defects of pristine MOFs and enlargement the capacity to a certain extent which accounts for the increment of conductivity and electron/ion transports capability. Furthermore, adding hierarchy to the MOFs structure using incorporating of carbon nanotubes can improve composite stability. Herein we synthesized interweaved MIL 68 (In) with multi wall carbon nanotubes (MIL 68 (In)-CNTs) composite and also we employ it as a template for In2 O3 porous hexagonal prisms hybridized with carbon nanotubes (In2 O3 PHP-CNTs). Facile solvothermal method and simple annealing treatment are used for these approaches. We investigate their electrochemical performance using a three-electrode cell system. Using cyclic voltammetry (CV) technique, MIL 68 (In)-CNTs electrode modifier exhibit the superior capacity of 601 Fg −1 at the speed rate of 5 mVs −1 . Besides, we assemble the symmetric supercapacitor (SSC) device via the MIL 68 (In)-CNTs nano platform. The synergistic effect between MIL 68 (In) and CNTs brings forth to an improved electrochemical performance with high energy and power density values of 13.3 Whkg −1 and 300 Wkg −1, respectively. This device shows high specific capacitance of 314 Fg −1 at 0.5 Ag −1, good rate capability and excellent cycling stability of 95% after 4000 cycles. Graphical abstract: Image, graphical abstract